Is The ‘ASEAN Economic Community’ Under Siege? The New Trajectory of the ASEAN Economic Community the two Mega Regional Agreements; “RCEP” and “TPP” - Kusumawardhana, Indra; Daniel, Jeremiah (RMPI-BRIN, 2017)
The ASEAN Economic Community (AEC) was signed by the leading nations of Southeast Asia in Kuala Lumpur on 31, December 2015. This was a great achievement of regional integration, pointing members of the AEC towards a single market “awakening”. Despite this tremendous progress, the reality is that ASEAN members are now involved in two mega-regional agreements. One, which has the potential to protect ASEAN centrality, ASEAN+6 or the Regional Comprehensive Economic Partnership (RCEP); and the other, the US-led Trans-Pacific-Partnership Agreement. This participation by ASEAN members with various economic partners outside ASEAN may result in dependency to global capitalism networks. Departing from the above mentioned context, the core question then arises: “Has the global economic structure provide an opportune precondition for the implementation of the ASEAN Economic Community (AEC)?” To tackle this question, this essay will use Dependency Theory to analyze the global economic structures which encase the AEC’s regional economic integration agenda and to reveal the ASEAN members’ dependence on global capitalism. This essay explores both the attempts of the ASEAN framework to create a comprehensive economic community; and the consequences of ASEAN integration with two mega-regional agreements in the region. It is argued that the dependency of ASEAN members on the structure of the global economy proves that it does not provide a proper pre-conditioning for the AEC to be implemented. Moreover, it will be hegemonic factors that challenge the existence of the AEC.